Medical treatment of weight loss in children and adolescents with obesity. (November 2022) - Calcaterra, Valeria; Rossi, Virginia; Mari, Alessandra; Casini, Francesca; Bergamaschi, Francesco; Zuccotti, Gian Vincenzo; Fabiano, Valentina
Abstract: Obesity remains one of the biggest health problems both in adults and children. Lifestyle modification, including diet and exercise, continues to be the mainstay of obesity prevention and treatment. Unfortunately, lifestyle modifications are often unsuccessful. Pharmacological treatment of obesity in pediatric patients can be applied in selected cases, and not before evidence of failure of the multidisciplinary lifestyle intervention. In this narrative review, we revised the most up-to-date evidence on medical treatment of weight loss in children and adolescents with obesity, including FDA- or EMA-approved and -experimented, not approved, drugs for pediatric population. Multidisciplinary treatment of childhood obesity, regulation of appetite control, energy balance and body weight were also discussed, in order to clarify the i ndications and mechanism action of drugs. Despite a substantial number of medications used for the treatment of obesity in adults, a limited number of drugs are approved by the drug regulatory agencies for pediatric population. Further research is needed to evaluate the efficacy and safety of novel pharmacological approaches for treatment of pediatric obesity in order to optimize weight management for children and adolescents and limit the development obesity-related comorbidities. Graphical Abstract: ga1